2022
DOI: 10.1007/s00345-022-04074-4
|View full text |Cite|
|
Sign up to set email alerts
|

Tadalafil monotherapy in management of chronic prostatitis/chronic pelvic pain syndrome: a randomized double-blind placebo controlled clinical trial

Abstract: Purpose In this placebo-controlled trial, we aimed to evaluate the clinical results of using PDE-5 inhibitor, tadalafil 5 mg OD, for management of CP/CPPS. Patients and methods 140 patients ≤ 45 years old with moderate/severe CP/CPPS associated with ED (IIEF-5 < 22) were randomly divided and received either tadalafil 5 mg OD (tadalafil-group) or placebo (control-group) for 6 weeks. Post-treatment CPSI scores were compared to baseline and to placebo. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…UTI was the common exclusion criterion of the selected studies. Detailed characteristics are mentioned in Table 1 [22][23][24][25][26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UTI was the common exclusion criterion of the selected studies. Detailed characteristics are mentioned in Table 1 [22][23][24][25][26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…Yamanishi et al [28] (2020) [29] (2022) Case: 39.9±3.9, Control: 39.7±4. 7 Type III Not reported 17.6±2.2 24.21±5.05…”
Section: Table 1: Characteristics Of the Selected Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…They improve lower urinary tract symptoms in men with benign prostatic hyperplasia, pulmonary arterial hypertension, complex regional pain syndrome and erectile dysfunction by relaxing the smooth muscle fibres of the prostate through modulation of nitric oxide cyclic guanosine monophosphate signalling. Studies have shown promising reductions in symptoms 15,16 …”
Section: Treatmentmentioning
confidence: 99%
“…Studies have shown promising reductions in symptoms. 15,16 Third-line: intravesical options Intravesical treatments include instillations of lidocaine, sodium hyaluronic acid, chondroitin sulphate, dimethyl sulfoxide (DMSO) and heparin, either alone or as combinations. They are usually given as a course, with more frequent instillations initially.…”
Section: Second-line: Oral Pharmacotherapiesmentioning
confidence: 99%